IFC in Indonesia : An Independent Country Impact Review - World Bank (World Bank, Washington, DC, 2012)
Independent Evaluation Group's (IEG's) Country Impact Review (CIR) evaluates International Finance Corporation's (IFC's) strategies and operations, and their outcome drivers in Indonesia, during fiscal year (FY) 1990-2006. The review covers the period before, during (FY 1998-2000) and after the most recent economic crisis. The CIR was prepared in parallel with the IEG Country Assistance Evaluation (CAE) of the World Bank's operations during FY 1998-2005, both are intended to inform the next World Bank Group Country Assistance Strategy (CAS) for Indonesia. While IFC's strategic priorities in Indonesia have been aligned with the country's private sector development needs, it has made little progress in supporting a larger private sector role in infrastructure and in helping deepen the financial markets. Increased private sector participation and IFC support for infrastructure development and for deepening the financial markets will depend on further government reforms. The CIR calls for a stronger IFC role in infrastructure and capital market development, including by strategically and operationally partnering with the World Bank and other Multilateral Development Banks (MDBs) to help dovetail sector reforms and investments. IFC needs to strengthen the environmental supervision of its Indonesian projects. The current compliance rate on environmental aspects is significantly below the institutional average and should be improved.